Impacting Digital Competence on Entrepreneurial Alertness: An Analytical Research at the Central Bank of Iraq - Khudhir Majeed, Isam; Adel Hamed, Suhair (Journal of Economics and Administrative Sciences, 2023)
In the era of the digital economy, public organizations need to consolidation the capabilities of entrepreneurial alertness to reduce the risks of sudden transformations and changes, and to find effective mechanisms to discover and invest in environmental opportunities proactively, as this concern has become a knowledge gap in public sector institutions, the current research aims to identify the role of digital competence in influencing on entrepreneurial alertness in the Central Bank of Iraq (CBI), the descriptive analytical approach was used as a research method to describe and analyze the main research variables. digital competence as an explanatory variable includes three dimensions: digital infrastructure, digital integration, and digital management, while entrepreneurial alertness as a responsive variable comprises three dimensions: scanning and search, association and connection, and evaluation as well as judgment. The research sample included the middle and senior administrative leaders of the CBI through using proportionate stratified random sampling to get a good representation of each class of society (n=125). The statistical package for social sciences (SPSS) and Structural Equation Modeling (SEM) by AMOS were used to analyze the research data. The results indicated that there is a statistically significant positive correlation and influence relationship between the two main research variables and their sub-dimensions. The most important dimensions of digital competence in influence and interest were digital infrastructure and digital management. However, the influence of digital integration on entrepreneurial alertness was insignificant in the CBI. Paper type: Research paper.